Evaluation of brachial plexus fascicles involvement on infraclavicular block: unfixed cadaver study - Gusmão,Luiz Carlos Buarque de (2015)
BACKGROUND AND OBJECTIVES: This study shows how the diffusion of the anesthetic into the sheath occurs through the axillary infraclavicular space and hence proves the efficacy of the anesthetic block of the brachial plexus, and may thereby allow a consolidation of this pathway, with fewer complications, previously attached to the anesthesia. MATERIALS AND METHODS: 33 armpits of adult cadavers were analyzed and unfixed. We injected a solution of neoprene with latex dye in the infraclavicular space, based on the technique advocated by Gusmão et al., and put the corpses in refrigerators for three weeks. Subsequently, the specimens were thawed and dissected, exposing the axillary sheath along its entire length. RESULTS AND DISCUSSION: Was demonstrated involvement of all fasciculus of the plexus in 51.46%. In partial involvement was 30.30%, 18.24% of cases the acrylic was located outside the auxiliary sheath involving no issue. CONCLUSIONS: The results allow us to establish the infraclavicular as an effective and easy way to access plexus brachial, because the solution involved the fascicles in 81.76% partially or totally, when it was injected inside the axillary sheath. We believe that only the use of this pathway access in practice it may demonstrate the efficiency.